2022
DOI: 10.1111/jace.18364
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and thermal shock properties of Cf/SiBCN composite: Effect of sintering densification and fiber coating

Abstract: In this work, resin-derived carbon coating was prepared on carbon fibers by polymer impregnation pyrolysis method, then silicoboron carbonitride powder was prepared by mechanical alloying, and finally carbon fiber-reinforced silicoboron carbonitride composites were prepared by hot-pressing process. The effects of sintering densification and fiber coating on microstructure, mechanical properties, thermal shock resistance, and failure mechanisms of the composites were studied. Fiber bridging hinders the sinterin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…The traditional method of preparing ceramics is to mix, shape, and sinter various raw material powders to obtain ceramic parts. However, due to the high temperature required for ceramic sintering, the shape, size, and properties are easily affected by the sintering process, and the ceramic itself is brittle and difficult to reprocess after sintering; therefore, some ceramics with high surface quality and precision are difficult to obtain by traditional preparation techniques [ 11 ]. 3D printing technology plays an important role in solving this problem.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The traditional method of preparing ceramics is to mix, shape, and sinter various raw material powders to obtain ceramic parts. However, due to the high temperature required for ceramic sintering, the shape, size, and properties are easily affected by the sintering process, and the ceramic itself is brittle and difficult to reprocess after sintering; therefore, some ceramics with high surface quality and precision are difficult to obtain by traditional preparation techniques [ 11 ]. 3D printing technology plays an important role in solving this problem.…”
Section: Literature Reviewmentioning
confidence: 99%
“…where u, T, T 0 , G c , c, and ρ are displacement, temperature, critical energy release rate, reference temperature, specific heat, and density, respectively; ε e = ε−ε T is the elastic strain tensor, where ε and ε T are total strain and thermal strain; 2 + δ is the degradation function, and δ is a parameter chosen to be as small as possible to ensure the problem converges; 𝜓 + 0 (𝜺 𝑒 ) and 𝜓 − 0 (𝜺 𝑒 ) are the tensile and compressive parts of the elastic energy density 23 :…”
Section: Phase-field Model For Thermal Shockmentioning
confidence: 99%
“…It is because changing α or E to x times and changing K IC to 1/x times will get the same phase-field evolution Equation (3). For example, when K IC becomes 1/x times, the energy release rate G c becomes 1/x 2 times the original value from 𝐺 𝐶 = 𝐾 2 𝐼𝐶 ∕𝐸, and the strain energy  remains unchanged. That is, G c :  = 1: x 2 .…”
Section: Effect Of Thermal Expansion Coefficient Young's Modulus or F...mentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with continuous carbon fiber reinforced polymer-derived SiBCN (PDCs-SiBCN) ceramic matrix composites (CMCs), [18][19][20][21] short carbon fibers are more suitable for the reinforcement of SiBCN ceramics prepared by mechanical alloying of mixed powders followed by sintering, 4,22,23 because short carbon fibers can be dispersed into mechanically alloyed SiBCN powders by a special sintering technique to obtain short carbon fiber reinforced mechanically alloyed SiBCN (MA-SiBCN) CMCs, denoted as C sf /SiBCN. [24][25][26][27] Zhu et al 26 fabricated C sf /SiBCN containing Zr by sintering under hot-pressing (HP) conditions at 1900 • C. The fracture surface (FS) showed limited fiber pull-out length due to severe interface reaction at high sintering temperatures, and the flexural strength decreased compared with the pure ceramics because of agglomeration and degradation of the carbon fibers. Niu et al 25 also adopted a similar method to obtain C sf /SiBCN and the results showed that many defects, such as pores and cracks, were formed due to uneven dispersion of the short fibers in the matrix as well as due to severe degradation of the fibers caused by interface reaction at high sintering temperatures.…”
Section: Introductionmentioning
confidence: 99%